A novel apparatus for time-lapse optical microscopy of gelatinisation and digestion of starch inside plant cells. (July 2020) - Do, Duc Toan; Singh, Jaspreet; Oey, Indrawati; Singh, Harjinder; Yada, Rickey Y.; Frostad, John M.
Abstract: A new instrument was developed for time-lapse optical microscopy of a cohort of individual food particles, which we denote as ParCS (Par ticle C ohort S tudy). The cohort can be observed through each stage of simulated hydrothermal processing, followed by in vitro gastrointestinal digestion. Instrument capabilities include the quantification of cooking and digestion dynamics of starch trapped inside isolated cotyledon cells from navy beans. The cells, contained within a flow-through chamber, were cooked at 90°C and subsequently subjected to simulated gastric digestion and simulated small-intestinal digestion. Little or no cell expansion was observed, and the cells remained intact, i.e., the cell walls showed no signs of rupture throughout the entire process. In contrast, intracellular starch granules partially swelled and gelatinised with a maximum relative granule area of approximately 2.4 at the end of cooking. During the small intestinal digestion, cellular contents were observed to visually "shrink" radially inwards towards the centre of the cells, implying that starch hydrolysis by pancreatic α-amylase had occurred inside the cells. Kinetic modelling of this shrinking process showed that the cells underwent amylolysis of cellular contents at different rates. This latter finding demonstrates that our new technique allows quantitative characterisation of starch gelatinisation and digestion inside cotyledon cells at the single-particle scale and may be used to test mechanistic hypotheses. Graphical abstract: Image 1 Highlights: A new instrument was devised for time-lapse optical microscopy of plant cells. Individual cells were tracked through each stage of simulated processing and digestion. The cooking and digestion dynamics of starch trapped inside cells were quantified. The instrument enables assessment of digestive behaviour at the single-particle scale.